Performance of a differential contrast sensitivity method to measure intraocular scattering - Pennos, Alexandros; Ginis, Harilaos; Arias, Augusto; Christaras, Dimitrios; Artal, Pablo (Biomedical optics express, 2017)
Increased intraocular scatter degrades quality of vision, especially in the presence of glare sources. Standard tests, such as visual acuity, are not well suited to capture this condition. There are specific methods to measure intraocular scatter, but require dedicated instruments. In this work, we propose a method to estimate the amount of scatter by combining to sequential measurements of the contrast sensitivity function for two conditions, with and without a glare source. We applied the approach in a group of young subjects with no know ocular pathology fitted with photographic diffusing filters. The straylight estimates were compared with those provided by two alternative techniques, one based on the compensation comparison method and the other the optical integration. The results obtained with the three approaches were in a good agreement, demonstrating the feasibility of the proposed method.